N100 Repetition Suppression Indexes Neuroplastic Defects in Clinical High Risk and Psychotic Youth - Joseph Gonzalez-Heydrich; Michelle Bosquet Enlow; Eugene D’Angelo; Larry J. Seidman; Sarah Gumlak; April Kim; Kristen A. Woodberry; Ashley Rober; Sahil Tembulkar; Kyle O’Donnell; Hesham M. Hamoda; Kara Kimball; et al. (Neural Plasticity)
Highly penetrant mutations leading to schizophrenia are enriched for genes coding for N-methyl-D-aspartate receptor signaling complex (NMDAR-SC), implicating plasticity defects in the disease’s pathogenesis. The importance of plasticity in neurodevelopment implies a role for therapies that target these mechanisms in early life to prevent schizophrenia. Testing such therapies requires noninvasive methods that can assess engagement of target mechanisms. The auditory N100 is an obligatory cortical response whose amplitude decreases with tone repetition. This adaptation may index the health of plasticity mechanisms required for normal development. We exposed participants aged 5 to 17 years with psychosis n=22, at clinical high risk (CHR) for psychosis n=29, and healthy controls n=17 to an auditory tone repeated 450 times and measured N100 adaptation (mean amplitude during first 150 tones − mean amplitude during last 150 tones). N100 adaptation was reduced in CHR and psychosis, particularly among participants <13 years old. Initial N100 blunting partially accounted for differences. Decreased change in the N100 amplitude with tone repetition may be a useful marker of defects in neuroplastic mechanisms measurable early in life.